Developmentally-Inspired Biomimetic Culture Models to Produce Functional Islet-Like Cells From Pluripotent Precursors - Tran, Raymond; Moraes, Christopher; Hoesli, Corinne A. (Frontiers in Bioengineering and Biotechnology, 2020)
Insulin-producing beta cells sourced from pluripotent stem cells hold great potential as a virtually unlimited cell source to treat diabetes. Directed pancreatic differentiation protocols aim to mimic various stimuli present during embryonic development through sequential changes of in vitro culture conditions. This is commonly accomplished by the timed addition of soluble signaling factors, in conjunction with cell-handling steps such as the formation of 3D cell aggregates. Interestingly, when stem cells at the pancreatic progenitor stage are transplanted, they form functional insulin-producing cells, suggesting that in vivo microenvironmental cues promote beta cell specification. Among these cues, biophysical stimuli have only recently emerged in the context of optimizing pancreatic differentiation protocols. This review focuses on studies of cell-microenvironment interactions and their impact on differentiating pancreatic cells when considering cell signaling, cell-cell and cell-ECM interactions. We highlight the development of in vitro cell culture models that allow systematic studies of pancreatic cell mechanobiology in response to extracellular matrix proteins, biomechanical effects, soluble factor modulation of biomechanics, substrate stiffness, fluid flow and topography. Finally, we explore how these new mechanical insights could lead to novel pancreatic differentiation protocols that improve efficiency, maturity, and throughput.